2004
DOI: 10.2527/2004.821218x
|View full text |Cite
|
Sign up to set email alerts
|

Improving pork quality by feeding supranutritional concentrations of vitamin D31

Abstract: Duroc-cross pigs (n = 25) were assigned to one of three experimental finishing diets containing 0 (control), 40,000 (40), or 80,000 (80) IU of supplemental vitamin D3/kg of feed (as-fed basis)to test the effects of vitamin D3 on pork quality traits. Experimental diets were fed for 44 or 51 d before slaughter, and days on feed were blocked in the experimental design. A trend existed for pigs receiving the highest concentration of vitamin D3 supplementation to have a lower (P = 0.08) ADG (0.77 kg/d) compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 16 publications
(23 reference statements)
2
50
0
3
Order By: Relevance
“…Additionally, the present study shows that the concentration of vitD 3 as a vitamin D source in the feed determines the concentration of vitD 3 in meat and liver even at small differences in the feeding levels, which was previously shown in pigs fed super nutritional levels at 1000 mg vitD 3 /kg 35 . Additional feeding trials are necessary to investigate fully the possibility of pork meat bio-fortified with vitamin D.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, the present study shows that the concentration of vitD 3 as a vitamin D source in the feed determines the concentration of vitD 3 in meat and liver even at small differences in the feeding levels, which was previously shown in pigs fed super nutritional levels at 1000 mg vitD 3 /kg 35 . Additional feeding trials are necessary to investigate fully the possibility of pork meat bio-fortified with vitamin D.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, for 8 days, which they attributed to higher proteolyses and instability of the muscle structure. Several studies on pork reported lower driploss when high supplement levels of vitaminD 3 were used (Enright et al, 1998, Lahucky et al, 2007and Wilborn et al, 2004. The study of Lahucky et al (2007) Paler meat, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…More studies previously reported that the supplementation with vitamin D 3 before slaughter to cattle improved meat color (Wilborn et al, 2004;Lobo et al, 2012), decreased shear force (Tipton et al, 2007;Moron et al, 2008). Another study indicated that supplementation with vitamin D 3 improved steak tenderness by affecting muscle Ca concentrations, μ-calpain activities, and muscle proteolysis (Montgomery et al, 2004).…”
Section: Meat Qualitymentioning
confidence: 99%